Sosialisasi Kegiatan Gerakan Masyarakat Hidup Sehat di Kota Tangerang Selatan - Novita, Wanda; Adi Supriyono , Lawrence; Hartanto, Prasetyo; Ardolof Toar, Yandri; Putri Andini, Siwi; Damas Ario Wicaksono, Dading; Juniarto, Antonius; Ramitha Janira Cindi (Community : Jurnal Pengabdian Pada Masyarakat, 2023)
The Healthy living community movement as known as GERMAS is a systematic and planned program that symergized with several ministries and institution. This program aims to increase people’s willingness and awareness to adopt a clean and healthy lifestyle and behavior, such as : physical activity, consuming fruits, and vegetables, and also regularly check up. This program (community service) was carried out in kota tangerang selatan, attended by 200 participants from various elements of the surrounding community, and reached an agreement to commit to healthy living, one of which was signing a healhy living commitment.